2021
DOI: 10.3389/fmed.2021.696597
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Recommendations to Combine Newer Therapies With Conventional Therapy in Psoriatic Disease

Abstract: Background: Psoriasis continues to have unmet needs in its management despite introduction of newer molecules. Monotherapy with these newer agents may not achieve therapeutic goals in all cases, hence necessitating their combinations with other molecules. Improved understanding of newer as well as conventional treatment modalities and experiences in their combinations hence necessitates therapeutic guidelines for their use in psoriasis.Objective: To review the combinations of treatments reported in literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 68 publications
(102 reference statements)
0
17
0
3
Order By: Relevance
“…Combined therapies, defined as treatment modalities involving combinations of two or more drugs, are used with three main aims: to increase the immediate and long‐term efficacy of each drug, ideally through synergistic effects; to reduce the toxicity of each drug; and, in some cases, to reduce costs by reducing the required dosages of each treatment 16–20 . Associations of topical and systemic treatments are used frequently in children and adults with psoriasis, and general recommendations for the use these combinations have been included in the management guidelines for childhood psoriasis 12–14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combined therapies, defined as treatment modalities involving combinations of two or more drugs, are used with three main aims: to increase the immediate and long‐term efficacy of each drug, ideally through synergistic effects; to reduce the toxicity of each drug; and, in some cases, to reduce costs by reducing the required dosages of each treatment 16–20 . Associations of topical and systemic treatments are used frequently in children and adults with psoriasis, and general recommendations for the use these combinations have been included in the management guidelines for childhood psoriasis 12–14 .…”
Section: Introductionmentioning
confidence: 99%
“…Combined therapies, defined as treatment modalities involving combinations of two or more drugs, are used with three main aims: to increase the immediate and long-term efficacy of each drug, ideally through synergistic effects; to reduce the toxicity of each drug; and, in some cases, to reduce costs by reducing the required dosages of each treatment. [16][17][18][19][20] Associations of topical and systemic treatments are used frequently in children and adults with psoriasis, and general recommendations for the use these combinations have been included in the management guidelines for childhood psoriasis. [12][13][14] Another combined therapy that has been included in the guidelines is the combination of acitretin with psoralen plus ultraviolet (UV)-A or narrow band UV-B therapy, which has been shown to lead to faster clearance of psoriasis and allow reductions in the doses of UV and acitretin, and thus increase the tolerance of both treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, adding apremilast to a biologic because of secondary drug failure has been described as a good alternative option. 12 In our series none of the patients with systemic combination treatment developed any adverse effects. However, with just four patients, we cannot extrapolate our findings.…”
Section: T a B L E 1 Patient Baseline Demographics And Clinical Chara...mentioning
confidence: 44%
“…[ 73 ] Also, it has been observed that the incidence of tumors was seven times higher after the first use of CsA as compared to that in the previous five years. [ 74 ] Additionally, findings from a systematic review by Arora et al ,[ 75 ] 2021 suggested not to recommend combination of cyclosporine and phototherapy due to greater chances of non-melanoma skin cancers.…”
Section: Resultsmentioning
confidence: 99%